Adsorptive removal of doxycyclIne hyclate from aqueous solution using KOH-modified iron-impregnated bamboo biochar. - Cruz, Joshua Antony
The concern regarding water contamination caused by doxycycline (DOX) has grown due to its negative health effects and the increasing evidence of the evolution of antimicrobial-resistant genes. In response, KOH-modified iron-impregnated biochar (KFBC) was synthesized from bamboo sawdust via modification/impregnation-pyrolysis process for the efficient removal of DOX from aqueous solution. KOH-modification successfully facilitated the formation of a more porous structure and promoted the addition of various surface functional groups as evident in SEM and FTIR analysis, respectively. Additionally, iron particles were effectively loaded onto the surface of the KFBC as confirmed by the EDS analysis. The point of zero charge of the KFBC was identified to be around 7.44. In the parametric study, it was determined that process factors such as adsorbent dosage, initial DOX concentration, and solution pH significantly influenced the removal of DOX. using the Box-Behnken design of experiment, a quadratic model best fitted the experimental data and was used to optimize the adsorption process parameters. The optimal DOX removal (97.51%) was obtained at operating conditions of adsorbent dosage (1.25 g L-1; minimize), initial DOX concentration (32 ppm; in range), and solution pH (3.0; in range). An actual removal efficiency of 98.74% using the optimized operating conditions validated the model at 95% confidence level. The adsorption kinetic data was well described by the pseudo-second-order kinetic model (0.9996), while the Redlich-Peterson model (0.9879) gave the best fit in DOX adsorption isotherm analysis. The maximum monolayer adsorption capacity of the KFBC was 95.02 mg g-1. These results indicate that DOX adsorption was mainly controlled by chemisorption on a heterogenous adsorbent surface. The possible mechanisms involved in DOX adsorption process are π-π interaction, electrostatic attraction, hydrogen bonding, and complexation reaction. These findings collectively suggest that KFBC serves as a highly effective adsorbent for the removal of emerging contaminants like doxycycline from aqueous solutions.